Gamifying a Simulation: Do a Game Goal, Choice, Points, and Praise Enhance Learning?. (October 2019) - Brom, Cyril; Stárková, Tereza; Bromová, Edita; Děchtěrenko, Filip
Despite the increased interest in gamification approaches, there is a lack of comparative studies that shed light on the applicability of these approaches in educational contexts. In this explorative study, with an experimental design, university learners ( N  = 98) studied a complex process (i.e., how to brew beer) in a 2-hour-long computerized simulation. In the experimental condition, the simulation featured the following game design elements: game goals, increased freedom of choice, points, virtual currency, and praise (i.e., a gamified simulation). These elements were absent in the simulation versions used in the two control conditions. No differences in learning outcomes and intrinsic motivation variables between the gamified simulation and its nongamified versions were observed. The gamified simulation was perceived to be significantly easier than the nongamified versions (η p 2  = 0.10; d  = 0.74, 0.42). Of the game elements used in this study, the participants perceived most positively a clear, game-like goal. The findings are consistent with self-determination theory, cognitive-affective theory of learning from media, and cognitive load theory. The findings also support the emerging notion that caution should be applied when using gamification approaches in educational contexts.